Scale‐aware camera localization in 3D LiDAR maps with a monocular visual odometry. (10th June 2019) - Sun, Manhui; Yang, Shaowu; Liu, Henzhu
Abstract: Localization information is essential for mobile robot systems in navigation tasks. Many visual‐based approaches focus on localizing a robot within prior maps acquired with cameras. It is critical where the Global Positioning System signal is unreliable. In contrast to conventional methods that localize a camera in an image‐based map, we propose a novel approach that localizes a monocular camera within a given three‐dimensional (3D) light detection and ranging (LiDAR) map. We employ visual odometry to reconstruct a semidense set of 3D points from the monocular camera images. These points are continuously matched against the 3D prior LiDAR map by a modified feature‐based point cloud registration method to track a full six‐degree‐of‐freedom camera pose. Since the monocular camera suffers from the scale‐drift problem due to the lack of depth information, the proposed method solves it by adopting updatable scale estimation. Experiments carried out on a publicly large‐scale data set demonstrate that the camera and LiDAR multimodal data matching problem is solved, and the localization accuracy of our method is comparable to state‐of‐the‐art approaches. Abstract : Monocular visual localization enables a robot to know its position at a low cost in places where the GPS signal is unreliable. A scale‐aware camera localization method in 3D LiDAR maps was proposed that using visual odometry to reconstruct 3D points to match against the LiDAR map. Experiments demonstrate that the camera and LiDAR multi‐modal data matching problem is solved and the localization accuracy of our method is comparable to state‐of‐the‐art approaches